Research of the selection of a gelling agent with further saturation of wipes with active prolonged effect - Semchenko, Kateryna; Buhai, Alina (Annals of Mechnikov’s Institute, 2022)
Introduction. During our research of the selection of gelling agents followed by saturation of wipes with an active prolonged effect, many factors should be considered. This fact may influence further drug development. The most important characteristics include the physical and chemical properties of studied gelling agents, the technological characteristics of these gelling agents, the quality of gels they form, their stability and safety, the possibility of choosing a gelling agent with an active pharmaceutical ingredient without any incompatibility. Also, one of the most important characteristics of studied gelling agents is their ability to form stable and homogeneous disperse systems, that should be easy to dissolve and make it possible to create series of gels with various viscosities. The aim of our work is to substantiate the selection of gelling agent for further saturation of wipes with an active prolonged effect. Materials and methods. As the objects of research were gelling agents, as well as the resulting samples of wipes that were based on them. For a more objective analysis, gelling agents were chosen by natural and synthetic origin. There were researched such gelling agents as apple pectin (natural origin), aristoflex (synthetic origin), xanthan gum (natural origin), carbopol (synthetic origin) and carbomer 940 (synthetic origin). Results and discussion. For the immobilization and fixation of gels when creating a wipe, the adsorption method, which is the easiest to perform and the most economically beneficial and essentially represents the saturation of the carrier with a saturating solution, was chosen [2]. Based on the biblio-semantic, physico-chemical and technological studies, a laboratory technology of material saturation was developed – a carrier that allows for maximum fixation of gelling agents on a wipe – the first saturation by immersion for 20 minutes, followed by wringing and drying, repeated saturation for 15 and 10 minutes with subsequent wringing and drying at temperature 75±5 ºС. 15 series of wipes samples based on selected gelling agents were investigated. The concentration of each gelling agent was established based on well-known technological recommendations and previously conducted scientific studies: apple pectin – 5.0 %, aristoflex – 0.5 %, xanthan gum – 1.0 %, carbopol – 0.5 %, carbomer 940 – 0,5 %. The mass of the wipe without saturation is 0.17 g. The saturation followed by drying was carried out in 3 stages. The obtained results indicate the following: Apple pectin: 5 minutes after the start of the experiment, saturation of the wipe with the gel almost does not occur, since subsequent saturations with a probability of 95 % fall into the confidence interval of the five-minute experiment [2,24;2,50]. The average percentage of drying is 52.79 %, which indicates an unsatisfactory result. Aristoflex: the maximum saturation of the wipe material with the gel occurs after 15 minutes, which with a probability of 95 % falls into the confidence interval [2.48; 3.02], and the calculated coefficients of variation confirm the correctness of the conducted experiment. The average percentage of drying is 29.75 %, which indicates an unsatisfactory result. Xanthan gum: the maximum saturation of the wipe material with the gel occurs after 15 minutes, which with a probability of 95 % falls into the confidence interval [2.45; 2.63], and the calculated coefficients of variation also confirm the correctness of the conducted experiment. The average percentage of drying is 35.65 %, which indicates an unsatisfactory result. Carbopol: the maximum saturation of the wipe material with the gel occurs after 15 minutes, which with a probability of 95 % falls into the confidence interval [2.45; 2.63], and the calculated coefficients of variation also confirm the correctness of the conducted experiment. The average percentage of drying is 20.21 %, which indicates a satisfactory result and the advisability of using carbopol to saturate wipes. Carbomer 940: the maximum saturation of the wipe material with gel occurs after 10 min, which with a probability of 95 % falls into the confidence interval [1.54; 2.29], and the calculated coefficients of variation also confirm the correctness of the conducted experiment. The average percentage of drying is 39.48 %, which indicates an unsatisfactory result. Therefore, it was found that the best organoleptic and technological characteristics among the presented samples were given by gelling agent of synthetic origin carbopol. It was experimentally found that this gelling agent has a low percentage of drying, as well as a high saturation coefficient compared to other gelling agents, presented in the samples. The additional statistical analysis showed that carbopol had many advantages in comparison with the other gelling agents. Conclusions. Based on the results obtained, carbopol is substantiated as the most prospect gelling agent for the further saturation of the wipes with an active prolonged effect. It has been experimentally proven that this gelling agent has all the necessary technological characteristics for the further development of a new drug based on carbopol. Keywords: apple pectin, aristoflex, xanthan gum, carbopol, carbomer 940, gelling agent, wipe, technology.